Quantitative estimates of time-averaging in terebratulid brachiopod shell accumulations from a modern tropical shelf - Carroll, M.; Kowalewski, M.; Simoes, M. G.; Goodfriend, G. A. (Paleontological Soc Inc, 2003)
Quantitative estimates of time-averaging in marine shell accumulations available to date are limited primarily to aragonitic mollusk shells. We assessed time-averaging in Holocene assemblages of calcitic brachiopod shells by direct dating of individual specimens of the terebratulid brachiopod Bouchardia rosea. The data were collected from exceptional (brachiopod-rich) shell assemblages, occurring surficially on a tropical mixed carbonate-siliciclastic shelf (the Southeast Brazilian Bight, SW Atlantic), a setting that provides a good climatic and environmental analog for many Paleozoic brachiopod shell beds of North America and Europe. A total of 82 individual brachiopod shells, collected from four shallow (5-25 m) nearshore (<2.5 km from the shore) localities, were dated by using amino acid racemization (D-alloisoleucine/L-isoleucine value) calibrated with five AMS-radiocarbon dates (r(2) = 0.933). This is the first study to demonstrate that amino acid racemization methods can provide accurate and precise ages for individual shells of calcitic brachiopods.The dated shells vary in age from modern to 3000 years, with a standard deviation of 690 years. The age distribution is strongly right-skewed: the young shells dominate the dated specimens and older shells are increasingly less common. However, the four localities display significant differences in the range of time-averaging and the form of the age distribution. The dated shells vary notably in the quality of preservation, but there is no significant correlation between taphonomic condition and age, either for individual shells or at assemblage level.These results demonstrate that fossil brachiopods may show considerable time-averaging, but the scale and nature of that mixing may vary greatly among sites. Moreover, taphonomic condition is not a reliable indicator of pre-burial history of individual brachiopod shells or the scale of temporal mixing within the entire assemblage. The results obtained for brachiopods are strikingly similar to results previously documented for mollusks and suggest that differences in mineralogy and shell microstructure are unlikely to be the primary factors controlling the nature and scale of time-averaging. Environmental factors and local fluctuations in populations of shell-producing organisms are more likely to be the principal determinants of time-averaging in marine benthic shelly assemblages. The long-term survival of brachiopod shells is incongruent with the rapid shell destruction observed in taphonomic experiments. The results support the taphonomic model that shells remain protected below (but perhaps near) the surface through their early taphonomic history. They may be brought back up to the surface intermittently by bioturbation and physical reworking, but only for short periods of time. This model explains the striking similarities in time-averaging among different types of organisms and the lack of correlation between time-since-death and shell taphonomy.